Simulated annealing of Skyrme model configurations - Magee, Shane (Trinity College (Dublin, Ireland). School of Mathematics, 2006)
The Skyrme model is a topological field theory that has been shown to be a good low energy approximation to QCD. A particular quantum theoretical treatment of the model reduces the quantization to a finite-dimensional quantum mechanical problem, selecting significant degrees of freedom of the configuration and quantizing them. A long-asked question has been how the quantized configuration differs from the classical minimum.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin